PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN KESIAPAN DAN PRESTASI BELAJAR SISWA (Studi Tindakan Kelas Pada Mata Pelajaran Bahasa Indonesia Kelas V SD Negeri 4 Merapi Selatan Kabupaten Lahat ) - Sukardi Sukardi (DIADIK, 2020)
Thisresearch aimstodescribethe applicationofcooperativetype of learning modeltalking stickto increasethereadinessandthe students’achievementat IndonesiansubjectofthefifthclassatSD Negeri4MerapiSelatan.Thedesignof researchusedisclassroomactionresearchandthequetiontexperiment.Thesubjects oftheresearcharethestudentsofV.aatthesecondsemesteroftheacademicyear 2019/2020atSDNegeri1MerapiSelatan.Forthesamplesof quetiontexperimentare V.b  and  V.c  nstrumen  penelitian  ini  menggunakanlembar  observasi  dan  tes.  The instrumentsusedisthe observationsheet andtest.The datais analizedwithusingthe statisticdescriptive,mean,thepercentageandT-test.The resultshowsthatthe application  of  cooperative  type  of  learning  model  talking  stick  can  increase  the readinessandthestudents’achievementofthestudentsofthefifthclassatSDNegeri 4Merapi SelatanLahatregency